RESHAPING WATERS. A HISTORY OF POLITICAL INTERFERENCE IN THE RISE AND FALL OF THE ROMANIAN SPA-TOWNS – CASE STUDY: SÂNGEORZ-BĂI - BORȘ, Silviu-Claudiu (Studia Universitatis Babeș-Bolyai Geographia, 2020)
A curious case in Romania’s architectural narrative is represented by its spa-towns, many of which have had seemingly regrettable fates. Once the crown jewels of the country’s tourism segment, only a few of this type of urban developments have retained their prestige, many of them being mere shadows of what they once were. Sângeorz-Băi, a small town in the northern county of Bistrița-Năsăud, falls somewhere in-between these two categories. By definition, spa-towns are resort towns developed on mineral springs that have appeared naturally and have been preserved for their health benefits. Seeing as the spa-town archetype is based on a commodity meant to be enjoyed by people, the interference of politics in the evolution of this type of urban entities came naturally. The proposed article means to explore how political interference affected the evolution of the aforementioned towns, Sângeorz-Băi being used as a case study that mirrors the ways in which political actors have affected the whole array of Romanian spa-towns. The entire intended discourse’s foundation would be based on reviewing the perks and misadventures that this type of towns have encountered through their existence, aspects that will be documented through archive studies, historical research and personal experience – the author of the intended article being a native of the spa-town Sângeorz-Băi, and also, in a way, a political actor himself, struggling to preserve some of the last historical buildings that the local authorities have yet to demolish (Fig.1).